A Buddhist future for capitalism? Revising Buddhist economics for the era of light capitalism. (April 2015) - Lennerfors, Thomas Taro
Highlights: Buddhism is neither solely a mental technique for coping with the side-effects of capitalism nor a philosophy of harmony. If Buddhist economics is rethought of as a critical philosophy, it can reform capitalism. A way to make Buddhist economics critical is to reinterpret The Four Noble Truths and The Eightfold Path. Such a turn to principles could be a way forward for arguments in the field of critical spirituality. Abstract: This paper discusses Buddhist economics as a potential future for capitalism. In the 1970s, EF Schumacher proposed a form of Buddhist economics aimed at smallness, simplicity and non-violence. The major contribution of the present paper is to revise and update Schumacher's and others' work on Buddhist economics, first because of the changing spirit of capitalism from heavy to light capitalism and, second, because Schumacher's critical perspective of Buddhism has not been sustained to the present day. Rather, Buddhism has been received in the West as a way of coping and as a harmonious philosophy. In order to face the future, the paper proposes a critical development of a Buddhist economics based on the principles of The Four Noble Truths and The Eightfold Path. Apart from revising and updating Buddhist economics, the paper engages in a discussion with the organizational spirituality literature, which contributes to the analysis, and to which contributions are made, first by dividing the field into critical–negative and critical–constructive approaches; and second, by proposing a turn to principles for critical–constructive approaches.